Old Mother Hubbard's dog dresses up - Yeoman, John (Boston : Houghton Mifflin Company, 1990)
When Old Mother Hubbard complains to her dog about the ragged condition of his coat, he resorts to wearing a variety of disguises and drives her to distraction.
Keywords: Dogs-Fiction; Stories in rhyme